Gut microbial signatures associated with the Indian lean MASLD phenotype - Dey, Priyankar (Frontiers in Nutrition, 2025)
Lean Metabolic Dysfunction-associated Steatotic Liver Disease (MASLD) is a substantial challenge in India, manifesting in individuals with normal BMI and indicative of a ‘metabolically obese normal weight’ phenotype. This review delineates the unique gut microbial signatures that characterize Indian lean MASLD, distinguishing it from obese MASLD. Principal modifications encompass substantial decreases in Faecalibacterium (particularly F. prausnitzii), Ruminococcus, Lactobacillus, Lachnospira, and Subdoligranulum, alongside an increase in pro-inflammatory Escherichia-Shigella. Dysbiotic patterns in India are influenced by factors such as fiber-deficient diets rich in refined carbohydrates, visceral obesity, insulin resistance, and genetic predispositions, including the PNPLA3 rs738409 polymorphism. Microbial alterations can contribute to disease by compromising gut barrier integrity, facilitating endotoxemia, and affecting the generation of beneficial metabolites. The combination signature of increased Escherichia-Shigella and decreased Lachnospira/Subdoligranulum exhibits significant diagnostic accuracy for detecting lean MASLD in the Indian population. These findings highlight lean MASLD as a mechanistically unique condition necessitating customized diagnostic and treatment approaches beyond standard weight management.